Cyber Security Issues Affecting the Users’ Willingness to Use E-Banking: A Case of Nepalese Commercial Banks - Joshi, Sulav Raj (Nepalese Journal of Economics, 2025)
This study examines the cyber security issues affecting the user willingness to use e-banking in Nepalese commercial banks. Willingness to use e-banking is selected as the dependent variable. Similarly, security and privacy concerns, fear of identity theft, fear of identity fraud, lack of trust and ease of use are selected as the independent variables. This study is based on primary data with 124 observation. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing e-banking users in Nepalese commercial banks. The study showed that security and privacy concerns has a positive impact on willingness to use e-banking. It means that increase in security and privacy concerns leads to increase in willingness to use e-banking. Similarly, fear of identity theft has a negative impact on willingness to use e-banking. It indicates that decrease in fear of identity theft leads to increase in willingness to use e-banking. Moreover, fear of identity fraud has a negative impact on willingness to use e-banking. It means that decrease in fear of identity fraud leads to increase in willingness to use e-banking. Likewise, lack of trust has a negative impact on willingness to use e-banking. It shows that decrease in lack of trust leads to increase in willingness to use e-banking. Similarly, ease of use has positive impact on willingness to use e-banking. It shows that higher the ease of use, higher would be the willingness to use e-banking.